Qualidade de gasolinas automotivas através de Espectroscopia vibracional FT-Raman, combinada com correlação 2D generalizada - Lima, Kellen Cristina Vilhena (2005)
It is reported the use of Generalized Two-Dimensional FT-Raman Correlation Spectroscopy (2DCOS-FT-Raman) method to monitor the quality of automotive gasoline in the gas stations. It is presented a procedure to identify the adulteration of automotive gasoline by the illicit addition of ethanol, methanol, aromatic and paraphinic compounds through the analysis of the Raman spectra obtained for different compositions of adulterants added to gasoline “A” type and to gasoline “A” type plus ethanol samples. It is discussed the data preconditioning step, the application of 2DCOS method, and the calibration curves that correlates the integrated intensities of the Raman bands of a given adulterant with its percentage in a given gasoline sample. It shown the protocol for using the 2DCOS-FT-Raman method to verify the adulteration in a given gasoline sample compared with a specific standard. This work emphasizes the flexibility and viability of using this method to have a specific standard for each gasoline distribution firm and also for each new gasoline derived from the refinery.